Secondary Intention Healing of Nasal Ala and Tip Defects: A Simple and Valuable Treatment Option - Wen G; Mao D; Zhu M; Hu J; Yao X; Zhang J (Dove Medical Press, 2022)
Guangdong Wen, Dandan Mao, Mengyi Zhu, Jian Hu, Xueyan Yao, Jianzhong Zhang Department of Dermatology, Peking University People's Hospital, Beijing, People's Republic of ChinaCorrespondence: Jianzhong Zhang, Department of Dermatology, Peking University People's Hospital, No. 11 Xizhimen South Street, Beijing, 100044, People's Republic of China, Tel +86-10-88325472, Email rmzjz@126.comPurpose: To investigate the cosmetic outcomes of secondary intention healing of small (< 1.5cm) nasal ala and tip defects.Patients and Methods: From August 2017 to October 2020, 42 patients with nasal reconstructions using secondary intention healing were included. Defects after excision ranged from 0.5cm× 0.7cm to 1.2cm× 1.5cm in size. Foam dressing covering the wounds was changed every 3 to 5 days. Wound esthetic outcomes were graded as excellent, good, acceptable, and poor based on definitions described in the literature.Results: All 42 wounds healed in 3 to 4 weeks, with uniform color, no obvious adverse reactions and high patient satisfaction. Esthetic evaluation: 16 excellent cases (38.1%), 19 good cases (45.2%), 7 acceptable cases (16.7%) and 0 poor cases.Conclusion: Secondary intention healing of small nasal tip and ala defects in Chinese yielded satisfactory esthetic outcomes and should be an integral part of the surgeon's reconstructive algorithm.Keywords: nasal tip, ala, secondary intention healing, foam dressing